2013
DOI: 10.1111/dote.12099
|View full text |Cite
|
Sign up to set email alerts
|

Association between coffee intake and gastroesophageal reflux disease: a meta-analysis

Abstract: Gastroesophageal reflux disease (GERD) is one of the most common diseases affecting patients worldwide, but its risk factors and causes are not clearly known. The aim of this study was to investigate the effect of coffee intake on GERD by a meta-analysis. We searched online published research databases such as PubMed, EMBASE, and Cochrane Library for studies that were published up to December 2012. These publications were reviewed by two independent authors, and studies that fulfilled the criteria were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 35 publications
5
33
1
6
Order By: Relevance
“…Although patients with GERD are often advised to avoid caffeine, 8 the current literature does not support an association between coffee and GERD. 9 Likewise, based on the findings of this study and in light of prior contradictory findings for EAC, 6,7 there does not appear to be an association between coffee and tea consumption and BE/EAC.…”
Section: Discussionsupporting
confidence: 42%
“…Although patients with GERD are often advised to avoid caffeine, 8 the current literature does not support an association between coffee and GERD. 9 Likewise, based on the findings of this study and in light of prior contradictory findings for EAC, 6,7 there does not appear to be an association between coffee and tea consumption and BE/EAC.…”
Section: Discussionsupporting
confidence: 42%
“…24,[28][29][30] Correlation with esophageal cancer remains unclear, too, with data on a protective effect of green tea, especially in studies conducted among Chinese population, 25 or a risk reduction only for subgroups of patients such as females. 31,32 Among the few studies on non-neoplastic esophageal diseases, a meta-analysis showed that overall coffee did not seem to be a causal factor for GERD, while a significantly higher odds ratio was found for E. 8 No association was found between coffee intake and the presence of BE in an our previous study; 33 furthermore, results from a US survey did not support an association between consumption of coffee or tea and the risk of BE. 6 No other data exist on the relationship between BE and tea consumption, but for a suggestion of green tea as an a potential chemopreventive agent for esophageal adenocarcinoma and BE because of the presence of polyphenols able to inhibit the growth of human Barrett's and aerodigestive adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 80%
“…[6][7][8] A recent study did not also support a correlation between tea intake and the risk of BE, 6 while there was a reduced risk of esophageal and other digestive cancers in Asian areas, at higher consumption of green tea. 9 On the other side, no association with cancers of the esophagus was found integrating a series of casecontrol studies conducted in Italy.…”
Section: Introductionmentioning
confidence: 92%
“…TiO 2 NPs and pepsin surface areas were calculated in order to estimate theoretically the number of pepsin that enough to cover the surface of one TiO 2 NP in one layer manner. The calculations recruit the TiO 2 NPs properties (radius = 9*10 -7 cm, density = 3.9 g/cm 3 , mass of one NP = ). From these parameters, the calculated surface areas of pepsin and TiO 2 NPs were 1.50*10 -13 cm 2 and 1.02*10 -11 cm 2 , respectively.…”
Section: Inhibition Of Pepsin Activity By Tio 2 Npsmentioning
confidence: 99%
“…GERD is a popular disease with a spread as 10%-20% in the western world [2]. GERD is one of the most common diseases affecting patients worldwide, but its risk factors and causes are not clearly known [3]. While the symptoms suggestive of gastroesophageal reflux (heartburn, reflux or chest pain) affect up to 30% of the population in Western countries and their prevalence continues to increase [4].…”
Section: Introductionmentioning
confidence: 99%